ACE2 and Furin Expressions in Oral Epithelial Cells Possibly Facilitate COVID-19 Infection via Respiratory and Fecal–Oral Routes - Zhong, Mei; Lin, Bingpeng; Pathak, Janak L.; Gao, Hongbin; Young, Andrew J.; Wang, Xinhong; Liu, Chang; Wu, Kaibin; Liu, Mingxiao; Chen, Jian-ming; Huang, Jiangyong; Lee, Learn-Han; et al. (Frontiers in Medicine, 2020)
Background: COVID-19 is caused by SARS-CoV-2 that mainly transfers from human to human via respiratory and gastrointestinal routes. The S-glycoprotein in the virus is the key factor for the entry of SARS-CoV-2 into the cell, which contains two functional domains: S1 is an ACE2 receptor binding domain and S2 is necessary for fusion of the coronavirus and cell membranes. Moreover, it has been reported that ACE2 is likely to be the receptor for SARS-CoV-2. In addition, mRNA level expression of FURIN enzyme and ACE2 receptor had been reported in airway epithelia, cardiac tissue, and enteric canals. However, the expression patterns of ACE2 and FURIN in different cell types of oral tissues are still unclear. Methods: In order to investigate the potential infective channel of new coronavirus via the oropharyngeal cavity, we analyze the expression of ACE2 and FURIN in human oral mucosa using the public single-cell sequence datasets. Furthermore, immunohistochemistry was performed in mucosal tissue from different oral anatomical sites to confirm the expression of ACE2 and FURIN at the protein level. Results: The bioinformatics results indicated the differential expression of ACE2 and FURIN on epithelial cells from different oral anatomical sites. Immunohistochemistry results revealed that both the ACE2-positive and FURIN-positive cells in the target tissues were mainly positioned in the epithelial layers, partly expressed in fibroblasts, further confirming the bioinformatics results. Conclusions: Based on these findings, we speculated that SARS-CoV-2 could invade oral mucosal cells through two possible routes: binding to the ACE2 receptor and fusion with cell membrane activated by FURIN protease. Our results indicated that oral mucosa tissues are susceptible to SARS-CoV-2 that could facilitate the COVID-19 infection via respiratory and fecal-oral routes.